A newly developed kit for dental apical root resorption detection: efficacy and acceptability - Jun Hong Steven Tan; Farinawati Yazid; Nurfathiha Abu Kasim; Shahrul Hisham Zainal Ariffin; Rohaya Megat Abdul Wahab (BMC, 2024)
Abstract Objectives To determine the efficacy of a newly developed kit in dentine sialophosphoprotein (DSPP) detection and compare it with enzyme-linked immunosorbent assay (ELISA). User acceptance was also determined. Materials and methods This cross-sectional study consisted of 45 subjects who were divided into 3 groups based on the severity of root resorption using radiographs: normal (RO), mild (RM), and severe (RS). DSPP in GCF samples was analyzed using both methods. Questionnaires were distributed to 30 orthodontists to evaluate future user acceptance. Results The sensitivity and specificity of the kit were 0.98 and 0.8 respectively. The DSPP concentrations measured using ELISA were the highest in the RS group (6.33 ± 0.85 ng/mL) followed by RM group (3.77 ± 0.36 ng/mL) and the RO group had the lowest concentration (2.23 ± 0.55 ng/mL). The new kit portrayed similar results as the ELISA, the optical density (OD) values were the highest in the RS group (0.62 ± 0.10) followed by RM group (0.33 ± 0.03) and the RO group (0.19 ± 0.06). The differences among all the groups were statistically significant (p < 0.05) for both methods. The Pearson correlation coefficient showed a statistically significant (p < 0.001) strong and positive correlation between DSPP concentrations and OD values. Conclusions The new kit was validated to detect the colour intensities of different severity of root resorptions. Most of the responses to the survey were positive towards the new kit for being a safer and simpler method to detect apical root resorption.